Психолого-педагогічний потенціал психологічного тренінгу в контексті спортивної діяльності гандболістів - Зогхламі, Ваель; Zohlamy, Wael (Східноєвропейський національний університет імені Лесі Українки, 2018)
Проведений аналіз наукової літератури дає підставу стверджувати, що тренінг є опосередкованою системою, котра може використовуватись індивідом у межах заданого контексту для управління власною діяльністю. Мета статті – теоретично обґрунтувати й емпірично довести необхідність впровадження експе-риментальної програми психологічного тренінгу вдосконалення психологічної готовності гандболістів. У контексті нашого дослідження тренінг розглядаємо як сукупність групових методів формування вмінь та навичок саморегуляції. Установлено, що психологічний вплив за допомогою ауторегуляторних прийомів допомагає створенню оптимальних внутрішніх умов, за яких ефективність рухової діяльності є найбільшою. Тренінг будується на оволодінні гандболістом конструктивними формами навчально-тренувальної та змагальної діяльності; техніками ауторелаксації й саморегуляції для зняття негативних імпульсів породження тривожності; поведінкових навичок за допомогою рольового розігрування поведінки в критичних обставинах; когнітивної здатності до аналізу ситуацій, власних переживань, до логічного пошуку способів розв’язання проблем. The problems of psychoprophylaxis and psycho-correction have been actively investigated recently, and this is due to the development of areas of practical sports psychology. As you know, the correction is the introduction of changes in a phenomenon that is characterized by static and certain devastating contradictory tendencies. The learning process does not coincide with the process of psycho-correction which is designed for the level of personality deformation, optimization of the relationship with the environment. And, although, psychocorrection and education are oriented towards the formation of personality, methods and means of achieving the goal in them are erroneous. The analysis of the scientific literature suggests that training is an indirect system that can be used by an individual within a given context for managing their own activities. The goal is to theoretically substantiate and empirically prove the need to introduce an experimental psychological training program to improve the psychological readiness of handball players. The objective is to theoretically substantiate and empirically prove the necessity of implementing an experimental program of psychological training for improving the psychological readiness of handball players. In the context of our study, training is considered as a set of group methods for the formation of abilities and skills of self-regulation. It has been established that psychological influence with the help of autoregulatory techniques helps to create optimal internal conditions under which the efficiency of motor activity is the greatest. Training is based on mastering a handball player in constructive forms of training and competitive activity; techniques of auto relaxation and self-regulation to relieve negative impulses causing anxiety; behavioral skills through role-playing behavior in critical circumstances; cognitive ability to analyze situations, their own experiences, to the logical search for ways to solve problems.
Psycho-Pedagogical Potential of Psychological Training in the Context of Sports Activities of Handball Players
Keywords: тренінг; психологічний стан; психологічна готовність; тривожність; training; psychological condition; psychological readiness; anxiety